A Note on a Strong Persistence of Stochastic Predator-Prey Model with Jumps - Olga Borysenko; Oleksandr Borysenko (Statistics, Optimization & Information Computing, 2023)
We study the non-autonomous stochastic predator-prey model with a modified version of Leslie-Gower term and Holling-type II functional response driven by the system of stochastic differential equations with white noise, centered and non-centered Poisson noises. The sufficient conditions of strong persistence in the mean of the solution to the considered system are obtained.